Is suffering Therapeutic? An exploration of buddhist ideas and Rogers' six conditions. (2nd July 2016) - Hayes, Cristalle
ABSTRACT: This article describes how clients experience, perceive, and respond to suffering and the tension that it can cause. I wish to explore the idea that there needs to be a shift in perception of what suffering is for the client in therapy. Can the suffering itself be therapeutic rather than problematic? Can having an understanding and resilience to endure suffering be the therapy? It is through my own experiences of suffering, through an understanding of Buddhist philosophy and the theory of Carl Rogers' Core Conditions and the phenomenological attitude that I am convinced of the therapeutic value of suffering. Since Buddhism engages deeply with the problem of suffering in such a profound way it seems absurd not to explore this philosophy to see what it can bring to my work with clients. Buddhist philosophy shows me a way to respond with compassion. It sets out a way to practice compassion through meditation, a way of being open to experience in a non-judgemental and accepting way. This reminds me of the ideas of phenomenology and also Carl Rogers' writings on the Core Conditions. I explore these ideas to establish how therapeutic suffering is and how we can respond to the suffering which is so ubiquitous in the therapeutic encounter.